EKSPLORASI PANGAN TRADISIONAL ACEH: KARAKTERISTIK IKAN DEPIK (Rasbora tawarensis) DAN PRODUK OLAHANNYA - Faidha Rahmi; Zulida Susanti; Cut Nilda; Murna Muzaifa (AGROINTEK, 2021)
Depik fish (Rasbora tawarensis) is an endemic freshwater fish typical of Lake Laut Tawar in Central Aceh. Gayo people usually buy depik fish in fresh or processed form in the form of dried depik and belacan depik. This research is a laboratory experimental study that aims to analyze the quality of depik fish and its processed products (fresh, dry and fermented depik fish). The parameters analyzed consisted of chemical analysis in the form of proximate analysis (moisture, ash, protein, fat and fiber content) and microbiological analysis by calculating the total plate count (TPC) of total mesophilic bacteria, lactic acid bacteria and fungi. The results showed that there were differences in the chemical and microbiological characteristics of depik fish with their processed products. Fresh depik has the highest water content, while dry depik has the highest fat and protein content. The highest ash content and fiber content were obtained at belacan depik. The highest total of mesophilic bacteria was obtained in fresh depik, while the highest total of lactic acid bacteria was obtained in fermentation depik. Fungal populations were only found in dry depicts and fermentation depik